MENINGKATKAN LITERASI LINGKUNGAN MELALUI PENGELOLAAN LIMBAH DI SMA NEGERI 6 KOTA TIDORE KEPULAUAN - Muna, Lintal; Muh. Amin, Astuti; Karmila, Fitriyah (Universitas Cokroaminoto Palopo, 2023)
Environmental literacy is knowledge, awareness, sensitivity and responsibility towards the environment. Someone who has good environmental knowledge, has a positive relationship with a good attitude towards his environment. This study aims to analyze environmental knowledge and environmental care attitudes of students through waste management at SMAN 6 Kota Tidore Kepulauan. This type of research is a quasi-experimental design with pretest and posttest. The research sample was class X students, totaling 38 students. The instruments used were multiple choice questions totaling 30 questions and the environmental care attitude questionnaire totaling 13 items. The instruments were tested using validity and reliability tests. Quantitative data analysis used the t test with the SPSS application. The results showed that environmental knowledge had different scores between the pre-test and the post-test. The same thing also happened to students' attitudes towards the environment. Based on the significant difference test with the Wilcoxon test, the value of students' environmental knowledge was 0.000 < 0.05, then H0 was rejected. This means that environmental knowledge through waste management in class X students of SMA Negeri 6 Tidore Kepulauan City differs significantly between before and after the learning process. The same thing happened with students' attitudes towards the environment with the t-test paired sample test, the result of which was a sig. (2-tailed) 0.000 < 0.05, so H0 is rejected. This means that there are significant differences in students' attitudes towards the environment before and after learning through waste management in class X SMA Negeri 6 Kota Ternate.